Increase in Deglacial Ocean Heat Content Linked to Contrasts in Extratropical Warming - Chenyu Zhu; Lijing Cheng; Zhengyu Liu; Peter U. Clark (Geophysical Research Letters, 2025)
Abstract Proxy‐based reconstructions suggest that equilibrium changes in global mean sea surface temperature (ΔGMSST) are nearly equivalent to changes in mean ocean temperature (ΔMOT) on glacial‐interglacial timescales over the past 900,000 years. However, the underlying mechanisms responsible for this relationship remain poorly understood. Here we use simulations from Paleoclimate Modeling Intercomparison Project Phase 3 and 4 (PMIP3/4) to investigate equilibrium ΔMOT and its linkage to sea surface temperature changes between the Last Glacial Maximum (LGM, ∼21,000 years ago) and pre‐Industrial. Results show that PMIP3/4 simulations generally underestimate proxy‐based ΔMOT. Regression analysis reveals that LGM MOT is strongly modulated by mid‐latitude SST cooling, with the Southern Ocean having a greater influence compared to other oceanic regions, thus helping explain why models with similar ΔGMSSTs exhibit significantly different ΔMOTs. Additionally, we find a strong relationship between simulated Antarctic sea‐ice coverage and Southern Ocean SST changes, with implications for constraining sea‐ice reconstructions.